Efficacy, safety and mechanism of Honghua Xiaoyao Pill in the treatment of peri-menopausal syndrome: A study protocol for a randomized controlled trial - Wu, Xiao; Zhou, Lishan; Dong, Haoxu; Tian, Man; Liu, Shiqin; Xu, Xiaohu (Frontiers in Pharmacology, 2022)
Background: Peri-menopausal syndrome (PMPS) has a high incidence rate and seriously affects the physical and mental health of women. Honghua Xiaoyao Pill (HHXYP) is a Chinese patent medicine, which has been reported to be used to treat PMPS. However, there is still a lack of randomized clinical trial to evaluate the efficacy and safety of HHXYP on life quality, mood and vasomotor symptoms for PMPS women. This study aims to investigate whether HHXYP is effective and safe in treating PMPS and the possible mechanism. Methods: A multicenter, randomized, controlled clinical trial will be conducted in China to evaluate the efficacy and safety of HHXYP. Sixty women with peri-menopausal syndrome will be recruited at three centers and randomly in a 1:1 ratio to a treatment group using HHXYP (HHXYP group) and a control group using oryzanol (OC group). Participants will be treated with HHXYP or oryzanol for 12 weeks and followed up for 4 weeks. The primary outcome is the modified Kupperman Index (KI), which will be measured at baseline and 4, 8, 12, 16 weeks after randomization. The secondary outcomes include Hot Flash scale (HFs), Menopause-Specific Quality of Life Scale (MENQOL) and Hamilton Depression/Anxiety Scale (HAMD/HAMA). The HFs are measured at the same point as the KI, other secondary outcomes are measured at baseline and 12, 16 weeks after randomization. The other outcomes are the levels of serum sex hormone, monoamine neurotransmitter, vascular vasomotor factor and the expression of phosphatidylinositol 3-active enzyme (PI3K)/protein activator enzyme B (Akt), which will be measured at baseline and 12 weeks after randomization. Adverse events will also be reported. Discussion: HHXYP is a potential alternative Chinese patent medicine for PMPS. This trial will provide evidence for HHXYP on improving the quality of life, mood and vasomotor symptoms, and sex hormone levels of PMPS patients.